El libro I de Conquiridores: edición y estudio. - ROMERO CAMBRÓN, ÁNGELES; CORTIJO OCAÑA, ANTONIO (Scripta)
Juan Fernández de Heredia (1310?-1396) promoted two major chronicles, that of Espanya and that of Conquiridores. The first partida of the latter has three copies: BNE 2211 (C1), from Avignon; BNE 12367 (C2, signed in 1454); and BNE 10190 (C3, a copy commissioned by Santillana). Conquiridores is an anthology of biographies of great warriors. Our objective is to present the life of Nino, the first of them. The text represents a complete novelty, as only one folio of this book has survived in C1, the only manuscript held at the Hispanic Seminary of Studies or in CORDE. We will offer the critical edition of C2. Book I opens and closes following Justin directly from the Latin. This very brief material alone would not be sufficient to form a book. Therefore, its central section has been augmented by a perfectly crafted compilation of materials. Our observations cannot be extended to the entire chronicle, which is large and remains to be studied. However, they do seem to indicate that C3 provides a different version of Conquiridores, perhaps an earlier one.